Dampak negatif leverage dan periode pandemi Covid-19 pada kinerja perusahaan sektor konstruksi di Indonesia - Robby Adam Fadlillah; Ossi Ferli (LPMP Imperium, 2024)
Company Size, Leverage, and the Anomalous Year of COVID-19 on the financial performance (ROA) of construction companies listed on the Indonesia Stock Exchange (2017-2022) using panel regression. The findings reveal that the CFO has no significant impact on ROA. At the same time, Leverage negatively affects ROA, and Company Size positively affects it. The COVID-19 Anomalous Year significantly and negatively influences financial performance, highlighting the pandemic’s disruptive effect. These findings offer insights into financial performance factors, emphasizing the importance of adaptive management strategies during uncertain economic conditions. Public interest statements This study provides insights for construction companies and the general public on how financial strategies such as leverage and company size affect financial performance, particularly during a crisis like COVID-19. The findings suggest that while larger companies may perform better, high leverage can pose risks, especially in unpredictable economic conditions. These insights can help companies develop adaptive strategies to survive economic disruptions, emphasizing the importance of balanced financial management.